(untitled) (Asian Journal of Medical and Biological Research, 2021)
Bisphenol-A (BPA) is one of the highest volume chemicals produced world-wide and used in the manufacture of plastics and epoxy resins that are pervasive in our environment and daily lives. The present research was carried out to investigate the effects of two different doses of Bisphenol-A (BPA) on the body weight, hematological parameters and patho-physiological changes of kidney in mice. For this study, fifteen mice, 6 to 8 weeks of age with an average bwt 27.10±0.5 gm, were randomly divided into three groups (n= 5). Group A (control) received only normal mouse pellet while group B and group C received pellet mixed with BPA @ 50 mg and 100 mg / kg bwt daily for 12 weeks, respectively. At the end of the experiment, blood and tissues were collected and processed for hematological and histopathological examination. Results showed that BPA- treated mice caused significant elevation (p<0.01) in weight gain even treated with low dose (50mg) of BPA. The mice exposed to high dose of BPA (100 mg) showed marked reduction (p<0.05) in total erythrocyte count (TEC), significant decreased (p<0.01) in hemoglobin concentration (Hb) and packed cell volume (PCV). Histopathological alterations were detected in the kidneys of BPA-treated mice. In conclusion, this study suggested that BPA exerts deleterious impacts on hematological parameters including association with renal injuries. Asian J. Med. Biol. Res. December 2020, 6(4): 635-640